Ovulation-inducing Effect of Angelica Sinensis Extract on Aged Infertile Mice and Its Impact on Fertility Capability - Wen Jiang; Weihui Yang; Li Li; Bingru Luo (Journal of Animal and Plant Sciences, 2025)
Although Angelica sinensis extract has been widely utilized for female reproductive health issues, its therapeutic effects on infertility are not established. This study aimed to assess the ovulation-inducing effects of Angelica sinensis extract in aged infertile mice and investigate its impact on fertility. An aged infertile mouse model was initially established and validated by monitoring estrous cycles. Subsequently, mice were randomly rolled into the control group (Group C) – receiving no intervention and being maintained under normal conditions; experimental group A (Group A) – establishing an infertility mouse model without any intervention; experimental group B (Group B) – constructing an infertility mouse model and administering Angelica sinensis extract as an intervention. Monitoring of hormonal levels, including estradiol (E2), anti-Mullerian hormone (AMH), luteinizing hormone (LH), follicle-stimulating hormone (FSH), progesterone (P), and testosterone (T), follicle counts, expression of proliferating cell nuclear antigen (PCNA), and primordial follicle activation-related proteins (YAP, p-YAP, mTOR, p-mTOR, rpS6, p-rpS6, PTEN, p-PTEN) were carried out to evaluate the impact of Angelica sinensis extract on mouse ovarian function. Simultaneously, fertility experiments were conducted to record pregnancy rates, litter sizes, and litter numbers for both groups of mice to investigate the impact of Angelica sinensis extract on fertility. Group A exhibited greatly lower E2, AMH, P, follicle count, PCNA protein expression, p-YAP/YAP ratio, p-mTOR/mTOR ratio, p-rpS6/rpS6 ratio, and higher levels of FSH, LH, T, p-PTEN/PTEN ratio, and the number of atretic follicles versus Group A (P ≤ 0.05). Group B showed higher levels of E2, AMH, P, PCNA protein expression, p-YAP/YAP ratio, p-mTOR/mTOR ratio, p-rpS6/rpS6 ratio, primordial follicles, primary follicles, and antral follicles, as well as lower levels of FSH, LH, T, p-PTEN/PTEN ratio, and the number of atretic follicles versus Group A (P ≤ 0.05). Group A exhibited a significantly decreased pregnancy rate, litter size, and litter number compared to Group C, while Group B showed a higher litter size and number than Group A (P ≤ 0.05).Angelica sinensis extract has a pronounced ovulation-inducing effect on aged infertile mice and can enhance their fertility. These findings suggest that Angelica sinensis extract might be a natural remedy for treating declining ovarian function.
Keywords: Angelica sinensis extract; aged; infertility; ovulation-inducing effect; ovaries; fertility capability